Green Coal Machine: Innovative Solution for Processing Organic Soil Enhancer from Compost and Coal Testing Waste - Rahayu, Lucky Putri; Yuliana, Vita; Budiono, M. Buang; Riznaldhy, Afrian; Kurniarina, Riris (Politeknik Negeri Batam, 2023)
The Eco Green Campus Program adopted by Sepuluh Nopember Institute of Technology (ITS) aims to create a campus that is sustainable and environmentally friendly with a focus on cultivating healthy organic soil. However, tillage Organic soil require organic materials which are quite expensive and difficult to obtain, such as organic fertilizer. Therefore, innovative solutions are needed through utilization of abundant local resources such as remaining coal samples with compost that called Green Coal which was made into quality organic soil enhancer. Coal has very complete nutrients and can be used as fertilizer. In addition, the use of coal as fertilizer can reduce the potential for degradation of the quality of agricultural land. In order to meet the needs in ITS parks, coal from the rest of the laboratory testing samples can also be used as a source of soil fertilizer. However, the results of the production is still lacking by number so sometimes the compost is applied though its still half ripe. To increase its effectiveness, organic compost waste is used as a soil conditioner through the use of coal. ITS has succeeded in developing a soil enhancer product named Green Coal from residual coal sample. However, the process of making Green Coal is done manually and is constrained by time constraints. Therefore, in this research, a 3-in-1 Green Coal machine was carried out to increase the efficiency of Green Coal production. The 3-in-1 Green Coal machine consists of a chopping machine, a sieving machine and a mixing machine in one machine so it can simplify processes, cost and time efficiency in the production process. The results of this research showed that a 3-in-1 Green Coal machine can produce 10 kg/minute of Green Coal soil enhancer products.